Strategi Kepala Madrasah Diniyah Dalam Meningkatkan Mutu Pendidikan Dan Minat Masyarakat Melalui Manajemen Humas Di Madrasah Diniyah Ar-Rohman Mlilir Dolopo Madiun - Muh Aris Umami; Samsudin Samsudin; Arik Dwijayanto (BASICA, 2023)
This study aims to describe the strategy of the head of Madrasah Diniyah Ar-Rohman in improving the quality of education and community interest through the implementation of public relations management. The research questions addressed are: (1) how is public relations management implemented at Madrasah Diniyah Ar-Rohman to improve the quality of education, (2) how is public relations management implemented at Madrasah Diniyah Ar-Rohman to increase community interest, (3) what is the impact of public relations strategies on community interest, and (4) what challenges are encountered in its implementation. This research uses a descriptive qualitative method with a case study approach, and data collection techniques include observation, interview, and documentation. The data were then analyzed using the Miles and Huberman method to obtain final research results. The results of the study show that: (1) public relations management at Madrasah Diniyah Ar-Rohman serves as a key strategy to enhance the quality of education through strengthening social relationships, increasing community participation, and fostering an open institutional climate. (2) Public relations activities at Madrasah Diniyah Ar-Rohman are carried out through socio-religious approaches such as Islamic study sessions (pengajian), Dzikrul Ghofilin and Khotmil Qur’an, communal work, and personal communication with students’ guardians and community leaders. (3) This public relations strategy has had a positive impact on increasing community interest, as indicated by the growing number of students and the community’s active involvement in madrasah activities. (4) However, its implementation faces several challenges, including limited resources, low awareness of the importance of education, and minimal use of modern media. The head of the madrasah addresses these issues by building social networks and engaging in effective direct communication.